Rene jornal ranked International Periodic: achievements and challenges in less than a decade old - Fraga, Maria de Nazaré de Oliveira; Cardoso, Maria Vera Lúcia Moreira Leitão (Rev Rene, 2007)
The Journal of Northeastern Nursing Network - RENE JOURNAL since March 2000 when it launched its first issue, is headquartered in the Nursing Department of the Federal University of Ceará. They have been published eight installments, totaling nineteen volumes, with extra issue containing your index. Regularity has been strong brand in the journal existence, because there was never gap in its publication. On the other hand, although slowly, growth in number of subscribers and also the growing influx of manuscripts allowed the intervals became more frequent.